Cytoskeletal Interactions at the Nuclear Envelope Mediated by Nesprins. (7th February 2012) - Taranum, Surayya; Sur, Ilknur; Müller, Rolf; Lu, Wenshu; Rashmi, R. N.; Munck, Martina; Neumann, Sascha; Karakesisoglou, Iakowos; Noegel, Angelika A.
Abstract : Nesprin-1 is a giant tail-anchored nuclear envelope protein composed of an N-terminal F-actin binding domain, a long linker region formed by multiple spectrin repeats and a C-terminal transmembrane domain. Based on this structure, it connects the nucleus to the actin cytoskeleton. Earlier reports had shown that Nesprin-1 binds to nuclear envelope proteins emerin and lamin through C-terminal spectrin repeats. These repeats can also self-associate. We focus on the N-terminal Nesprin-1 sequences and show that they interact with Nesprin-3, a further member of the Nesprin family, which connects the nucleus to the intermediate filament network. We show that upon ectopic expression of Nesprin-3 in COS7 cells, which are nearly devoid of Nesprin-3 in vitro, vimentin filaments are recruited to the nucleus and provide evidence for an F-actin interaction of Nesprin-3 in vitro. We propose that Nesprins through interactions amongst themselves and amongst the various Nesprins form a network around the nucleus and connect the nucleus to several cytoskeletal networks of the cell.